Effects of a restrictive blood transfusion protocol on acute pediatric burn care: transfusion threshold in pediatric burns - Voigt, Charles D.; Hundeshagen, Gabriel (The journal of trauma and acute care surgery, 2018)
BACKGROUND: Blood transfusion is costly and associated with various medical risks. Studies in critically ill adult and pediatric patients suggest that implementation of more restrictive transfusion protocols based on lower threshold hemoglobin concentrations can be medically and economically advantageous. The purpose of this study was to evaluate the implications of a hemoglobin threshold change in pediatric burn patients. - METHODS: We implemented a change in hemoglobin threshold from 10 g/dL to 7 g/dL and compared data from patients before and after this protocol change in a retrospective review. Primary endpoints were hemoglobin concentration at baseline, before transfusion, and after transfusion; amount of blood product administered; and mortality. Secondary endpoints were the incidence of sepsis based on the American Burn Association physiological criteria for sepsis and mean number of septic days per patient. All endpoint analyses were adjusted for relevant clinical covariates via generalized additive models or Cox proportional hazard model. Statistical significance was accepted at p less than 0.05. - RESULTS: Patient characteristics and baseline hemoglobin concentrations (pre, 13.5 g/dL; post, 13.3 g/dL; p > 0.05) were comparable between groups. The group transfused based on the more restrictive hemoglobin threshold had lower hemoglobin concentrations before and after transfusion throughout acute hospitalization, received lower volumes of blood during operations (pre, 1012 mL; post, 824 mL; p < 0.001) and on days without surgical procedures (pre, 602 mL; post, 353 mL; p < 0.001), and had a lower mortality (pre, 8.0%; post, 3.9%; mortality hazard decline, 0.55 [45%]; p < 0.05). Both groups had a comparable incidence of physiological sepsis, though the more restrictive threshold group had a lower number of sepsis days per patient. - CONCLUSION: More restrictive transfusion protocols are safe and efficacious in pediatric burn patients. The associated reduction of transfused blood may lessen medical risks of blood transfusion and lower economic burden. - LEVEL OF EVIDENCE: Therapeutic, level IV.
Gesehen am 27.03.2019